Telemedicine for allergic patients during COVID‐19. (24th November 2020) - Pattini, Stefano; Malizia, Velia; Travaglini, Alessandro; Brighetti, Maria Antonia; Della Giustina, Auro; Sfika, Ifigenia; Di Menno Di Bucchianico, Alessandro; Tripodi, Salvatore
Abstract: In the last few years, we have witnessed an important development in the medical field of both Mobile Health, such as the use of mobile communication devices, and other telemedicine tools in general, in order to support the surveillance of diseases from the moment of the first diagnosis to the therapeutic follow‐up. Long before COVID‐19, some authors had analyzed various possible evidence‐based scenarios and had indicated how the use of telemedicine could prove to be extremely useful in epidemic situations, especially for the management of chronic patients, such as immune‐allergic ones, who are notoriously in greater need of regular follow‐up; however, as expected, the advent of the COVID‐19 pandemic has amplified the differences between various countries, from the point of view of the propensity to use technological solutions in the health sector. The hope is that one positive outcome of the ongoing pandemic is that it will lead to an acceleration, by all the stakeholders involved, of the process of modernization of health care.